The multi-ethnic character of medieval Silesian society and its influence on the region’s cohesion (12th–15th centuries) - Wiszewski, Przemysław (Publishing House eBooki.com.pl, 2013)
From the end of the 13th century the number of German settlers rapidly grew in what had been a mostly Polish-speaking community of Silesians. Piotr Górecki indicated that the presence of newcomers from Germany in the Piast realm led to an assimilation that did not involve the complete adoption of the norms of one ethnic group by another. On the contrary, those involved in these relations acknowledged the differences between the two groups. At the same time, in order to avoid conflict it was important to gain knowledge about the other group, thus enabling the stable coexistence of the two communities in the same territory. However, this well-proven hypothesis leaves open the question of how this dynamic process affected regional cohesion. Did it lead to the strengthening of local communities by forcing their members to focus on cooperation in the local context, ignoring the broader regional setting? Or perhaps, on the contrary, the need to mediate between groups of different cultural and linguistic backgrounds stretched beyond local boundaries? Dynamically changing ethnic relations in Silesia between the 13th and 15th centuries had a mixed impact on the cohesion of the regional community. This diversity ultimately strengthened the sense of the region’s separateness from its neighbours. A common administrative framework set up in the 15th century did not, in the eyes of contemporaries, overshadow the specificity of the multiethnicity, multilingualism and inter-ethnic relationships within Silesian society. These were perceived as unique when contrasted with similar phenomena taking place in neighbouring countries. At the local level, the possibility to make reference to the situation in the region as a whole when resolving ethnic conflicts sustained awareness of the importance of the regional dimension in the proper functioning of the local community. This was not a static system. Silesians demonstrated diverse perceptions and attitudes towards multiethnicity and the impact of this phenomenon on the cohesion of various communities operating within the region was diverse as well. A presentation of these phenomena in the context of time and in the pragmatic perspective of the sources describing them paves the way for a new approach towards Silesian multiethnicity as a dynamic phenomenon which does not necessarily take one course throughout the entire territory.
Keywords: multiethnicity; multilingualism; inter-ethnic relations